Film Animasi 2 Dimensi Cerita Rakyat Bali Berjudul I Ceker Cipak - Benny Muhdaliha; Dewa Ray Dharmayana Batuaya (LPPM Institut Bisnis dan Teknologi Indonesia, 2017)
Many factors can lead to moral irregularities by children, one of which is the number of impressions that are less culturally appropriate and less educational for children. Impressions adapted from folklore often become a strategic alternative as educational media. In general, the message conveyed in folklore is a guideline of behavior in social life, good and bad teaching, joy, sadness, and heroism. Positive moral messages contained are expected to control turbulent in emotion and character development in the process of forming a child's character, especially in the contemporary era. 2 dimensional (2D) animated film which delivering Balinese local content from folklore is done by this research. The 2D animation is entitled 'I Ceker Cipak'. The 2D animation form is chosen because it can explain complicated information to be more simple and interesting, so it can be easily to understood by the audience. 2D animated film is also a media that can be enjoyed by all ages and relatively cheaper and easy to use. Story I Ceker Cipak also convey the values ​​of justice, and humanity through the implementation of the law of karma phala. From the results of tests conducted on children SDN 1 Semarapura Middle students, Klungkung, found that elementary school children can easily understand the moral messages contained in the 2D animation folklore movie entitled I Ceker Cipak.